Management of Anterior Cruciate Ligament Rupture: A Narrative Review of Emerging Therapeutic Methods - Matczak, Simon; Namysł, Maria; Sobkowiak, Marcin; Woźniak, Kinga; Bieniek, Maciej; Żukowski, Marcel; Modelski, Mikołaj; Osada, Julia; Dzierbicka, Nikola; Kulpa, Agnieszka (Quality in Sport, 2026)
​​Background. Anterior cruciate ligament (ACL) rupture is a common orthopedic injury that significantly impacts athletic performance and long-term joint stability. While surgical reconstruction (ACLR) remains the current gold standard, there are concerns regarding graft failure, persistent rotational laxity, and the development of post-traumatic osteoarthritis. Aim. This narrative review aims to analyze emerging therapeutic methods in ACL management, including modern surgical techniques, orthobiologic therapies, and tissue engineering, in terms of their clinical efficacy and limitations regarding their implementation in clinical practice. Methodology. A literature search was conducted using PubMed, Web of Science, and Google Scholar. Meta-analyses, randomized controlled trials, and systematic reviews focusing on innovative therapeutic methods for ACL injuries were included. Results. Primary repair with internal bracing and bridge-enhanced ACL repair technique show promise in joint preservation but are strictly dependent on tear morphology. Extra-articular augmentation have potential to reduce rotational laxity in high-risk cohorts. Platelet-rich plasma and mesenchymal stem cells may promote "ligamentization," though clinical evidence remains inconsistent due to a lack of standardized preparation protocols. Tissue engineering techniques, such as 3D bioprinting and electrospinning offer biomimetic potential, although there are significant regulatory and economic barriers. Conclusions. Emerging therapeutic methods in ACL injury management offer promising advantages when combined with traditional ACLR. However, their widespread implementation is currently limited by high costs, a lack of long-term clinical data, and the need for standardized application protocols. Future research is needed to determine the long-term effectiveness of these techniques and to define their precise role in routine clinical practice.